Женские погребения Николаевского могильника - Сикоза, Д.Н.; Дзнеладзе, Е.С. (Археологія і давня історія України, 2019)
Статья посвящена анализу 54 женских погребений, раскопанных в 1960—70 гг. экспедицией
Э. А . Сымоновича на позднескифском Николаевском могильнике Бериславского р-на Херсонской
обл. В статье рассмотрена хронология комплексов и особенности погребального обряда. 54 female burials from Late Scythian Nikolaevka
burial ground of Kherson district are analyzed in the
paper. They were excavated by Erast Symonovich expedition
during 1960—1970.
The analysis of materials from female burials
showed that Nikolaevka burial ground was in use
during all chronological period of local Lower Dnieper
variant of the Late Scythian culture. Female burials
reflected the periods of origin, heyday and decline of this burial ground.
The funerary rite and grave goods are typical for the Late Scythian culture, and have analogies among
the materials of the Zolotaya Balka, Krasnyi Mayak, the necropolises of Tanais, Nikoniy, the Scythian Neapolis
and Zolotoye. Female burials traditionally contained personal items: bronze mirrors, brooches, awls
and knives, beads, earrings, bracelets and rings. There are unique finds in the Nikolaevka burial ground: rare
types of terra sigilata pottery, beads from semiprecious stones, the ring with a portrait gem, bronze tweezers.
The square catacombs, unusual for the Lower Dnieper variant of the Late Scythian culture, were recorded
in the Nikolaevka burial ground. In our opinion, these catacombs can be a marker of the migration of
part population from the south-western Crimea to the Lower Dnieper in the first centuries AD.